Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To write the quadratic equation in Vertex Form given a vertex at [tex]\((-5, 1)\)[/tex] and a point through which the parabola passes [tex]\((-4, 5)\)[/tex], we can follow these steps:
1. Understand the Vertex Form: A quadratic equation in vertex form is given by:
[tex]\[ y = a(x - h)^2 + k \][/tex]
Here, [tex]\( (h, k) \)[/tex] is the vertex of the parabola, and [tex]\(a\)[/tex] is a coefficient that determines the width and direction of the parabola.
2. Substitute the Vertex Coordinates: Given the vertex [tex]\((-5, 1)\)[/tex], we substitute [tex]\( h = -5 \)[/tex] and [tex]\( k = 1 \)[/tex] into the vertex form equation:
[tex]\[ y = a(x + 5)^2 + 1 \][/tex]
3. Use the Given Point to Find [tex]\(a\)[/tex]: We know the parabola passes through the point [tex]\((-4, 5)\)[/tex]. So, we substitute [tex]\( x = -4 \)[/tex] and [tex]\( y = 5 \)[/tex] into the equation:
[tex]\[ 5 = a(-4 + 5)^2 + 1 \][/tex]
4. Simplify and Solve for [tex]\(a\)[/tex]: Calculate the expression:
[tex]\[ 5 = a(1)^2 + 1 \][/tex]
[tex]\[ 5 = a + 1 \][/tex]
Subtract 1 from both sides:
[tex]\[ 4 = a \][/tex]
So, the value of [tex]\(a\)[/tex] is 4.
5. Write the Complete Equation: Now that we have determined [tex]\( a = 4 \)[/tex], we substitute it back into the vertex form equation:
[tex]\[ y = 4(x + 5)^2 + 1 \][/tex]
So, the quadratic equation in Vertex Form is:
[tex]\[ y = 4(x + 5)^2 + 1 \][/tex]
1. Understand the Vertex Form: A quadratic equation in vertex form is given by:
[tex]\[ y = a(x - h)^2 + k \][/tex]
Here, [tex]\( (h, k) \)[/tex] is the vertex of the parabola, and [tex]\(a\)[/tex] is a coefficient that determines the width and direction of the parabola.
2. Substitute the Vertex Coordinates: Given the vertex [tex]\((-5, 1)\)[/tex], we substitute [tex]\( h = -5 \)[/tex] and [tex]\( k = 1 \)[/tex] into the vertex form equation:
[tex]\[ y = a(x + 5)^2 + 1 \][/tex]
3. Use the Given Point to Find [tex]\(a\)[/tex]: We know the parabola passes through the point [tex]\((-4, 5)\)[/tex]. So, we substitute [tex]\( x = -4 \)[/tex] and [tex]\( y = 5 \)[/tex] into the equation:
[tex]\[ 5 = a(-4 + 5)^2 + 1 \][/tex]
4. Simplify and Solve for [tex]\(a\)[/tex]: Calculate the expression:
[tex]\[ 5 = a(1)^2 + 1 \][/tex]
[tex]\[ 5 = a + 1 \][/tex]
Subtract 1 from both sides:
[tex]\[ 4 = a \][/tex]
So, the value of [tex]\(a\)[/tex] is 4.
5. Write the Complete Equation: Now that we have determined [tex]\( a = 4 \)[/tex], we substitute it back into the vertex form equation:
[tex]\[ y = 4(x + 5)^2 + 1 \][/tex]
So, the quadratic equation in Vertex Form is:
[tex]\[ y = 4(x + 5)^2 + 1 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.